The Influence of Sharia Accounting Understanding and the Use of Accounting Applications on the Quality of Financial Reporting - Maulidia, Riza; Risnaeni, Umi Suswati; Farid, Muhammad; Urmila, Titin; Sulhani, Sulhani (Tazkia Islamic University College, 2025)
This study aims to analyze the influence of Sharia accounting understanding and the use of accounting applications on the quality of financial reporting preparation based on Sharia Financial Accounting Standards (SFAS) at The National Board of Zakat (Badan Amil Zakat Nasional or BAZNAS) Lumajang. This research employs a quantitative method by collecting data through surveys and statistical analysis. The results indicate that Sharia accounting understanding significantly affects the quality of financial report preparation at BAZNAS. Furthermore, the use of accounting applications also has a significant impact on improving the quality of financial reporting preparation based on SFAS. These findings highlight the importance of Sharia accounting knowledge and technology utilization in enhancing financial reporting quality in zakat management institutions.